2017
DOI: 10.1016/s2215-0366(17)30127-x
|View full text |Cite|
|
Sign up to set email alerts
|

Architecture and functioning of child and adolescent mental health services: a 28-country survey in Europe

Abstract: The WHO Child and Adolescent Mental Health Atlas, published in 2005, reported that child and adolescent mental health services (CAMHS) in Europe differed substantially in their architecture and functioning. We assessed the characteristics of national CAMHS across the European Union (EU), including legal aspects of adolescent care. Using an online mapping survey aimed at expert(s) in each country, we obtained data for all 28 countries in the EU. The characteristics and activities of CAMHS (ie, availability of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 32 publications
4
101
0
7
Order By: Relevance
“…However, it is important to acknowledge the broader context of system-level issues in mental healthcare systems that may constrain their effective implementation. CAMHS and AMHS are two separate systems with unique funding structures, service philosophies and target populations [1,37,58,109]. Government funding allocations often dictate rigid age cut-offs, where service with CAMHS often ends at age 18 regardless of whether the youth is developmentally ready or connected to AMHS [1,5,72,104].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to acknowledge the broader context of system-level issues in mental healthcare systems that may constrain their effective implementation. CAMHS and AMHS are two separate systems with unique funding structures, service philosophies and target populations [1,37,58,109]. Government funding allocations often dictate rigid age cut-offs, where service with CAMHS often ends at age 18 regardless of whether the youth is developmentally ready or connected to AMHS [1,5,72,104].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Finland has a higher number of child and adolescent psychiatrist per each young person compared to Denmark (36.0 vs. 10.3 per 100,000 persons) [40], and therefore, young people with depression may have better access to specialized care in Finland. When we analyzed cases of moderate or severe depression assessed at two visits or more, we found that the number of cases dropped by half.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 28-country survey of child and adolescent mental health services in Europe showed substantial heterogeneity of inpatient beds among these countries. The number of inpatient beds for youth ranged from fewer than two beds per 100000 young people in Portugal and Sweden to more than 50 beds per 100000 young people in Germany and the Netherlands [28]. The situation seemed worse in low-income and middle-income countries.…”
Section: Critical Shortage In Youth Psychiatric Bedsmentioning
confidence: 99%